(untitled) (International Seven Journal of Multidisciplinary, 2025)
We apply a new tool that is the Maxwell-Fredholm equations, to study the collision of an electromagnetic pulse with a flat surface of separation between the two parts of a torus-shaped artefact with a highly anisotropic refractive index that forces it to move over its surface. We find that it is possible to establish a relationship between the different angles involved depending on the parameters of the toroidal coordinates, which we call a particularization of Snell’s law.